A Comparison of Enhancement Techniques for Footwear Impressions on Dark and Patterned Fabrics1, 2. Issue 6 (20th June 2013) - Farrugia, Kevin J.; Bandey, Helen; Dawson, Lorna; Daéid, Niamh Nic
Abstract: The use of chemical enhancement techniques on porous substrates, such as fabrics, poses several challenges predominantly due to the occurrence of background staining and diffusion as well as visualization difficulties. A range of readily available chemical and lighting techniques were utilized to enhance footwear impressions made in blood, soil, and urine on dark and patterned fabrics. Footwear impressions were all prepared at a set force using a specifically built footwear rig. In most cases, results demonstrated that fluorescent chemical techniques were required for visualization as nonfluorescent techniques provided little or no contrast with the background. Occasionally, this contrast was improved by oblique lighting. Successful results were obtained for the enhancement of footwear impressions in blood; however, the enhancement of footwear impressions in urine and soil on dark and patterned fabrics was much more limited. The results demonstrate that visualization and fluorescent enhancement on porous substrates such as fabrics is possible.